2015
DOI: 10.1021/mz500748f
|View full text |Cite
|
Sign up to set email alerts
|

Phase Separation and Nanodomain Formation in Hybrid Polymer/Lipid Vesicles

Abstract: International audienceHybrid polymer/lipid large unilamellar vesicles (LUVS) were studied by small angle neutron scattering (SANS), time-resolved Forster resonance energy transfer (TR-FRET), and cryo-transmission electron microscopy (cryo-TEM). For the first time in hybrid vesicles, evidence for phase separation at the nanoscale was obtained, leading to the formation of stable nanodomains enriched either in lipid or polymer. This stability was allowed by using vesicle-forming copolymer with a membrane thicknes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
100
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(105 citation statements)
references
References 31 publications
5
100
0
Order By: Relevance
“…Both Nallani and co‐workers and Kroeger and co‐workers have previously reported that LUVs can be formed that co‐localize lipids and block co‐polymers in each vesicle. However, the existence of nanoscale phase separation could only be demonstrated recently by Le Meins and co‐workers in triblock PEO‐PDMS‐PEO/phospholipid LUV, which show phase separation at all temperatures, using SANS and FRET . Our measurements address PBD‐ b ‐PEO/phopspholipid LUVs, for which lipid domain formation in GUVs only occur below the lipid T m .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Both Nallani and co‐workers and Kroeger and co‐workers have previously reported that LUVs can be formed that co‐localize lipids and block co‐polymers in each vesicle. However, the existence of nanoscale phase separation could only be demonstrated recently by Le Meins and co‐workers in triblock PEO‐PDMS‐PEO/phospholipid LUV, which show phase separation at all temperatures, using SANS and FRET . Our measurements address PBD‐ b ‐PEO/phopspholipid LUVs, for which lipid domain formation in GUVs only occur below the lipid T m .…”
Section: Resultsmentioning
confidence: 99%
“…Given that we have shown that USPIONs can efficiently be loaded at high weight fraction by solvent inversion into both liposomes and PBD‐ b ‐PEO polymersomes (above and ), the most likely reason for the reduced fraction of released cargo is an inhomogeneous distribution of lipid between vesicles. Inhomogeneous distribution of lipids in hybrid LUVs was recently observed using flow cytometry by Le Meins and co‐workers for triblock copolymer and lipids both above and below the lipid T m . Domains that are large enough to yield release will not form at too low lipid fractions in the individual vesicles …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[43,[51][52][53][54][55][56][57][58] Understanding how to harness biophysical properties of bilayer membranes to expand their functionality beyond containment alone is an important step in the design of artificial cellular systems. Domains have been recapitulated and characterized in both lipid and polymer systems.…”
Section: Forschungsartikel Discussionmentioning
confidence: 99%